2016
DOI: 10.1007/s00345-016-1837-z
|View full text |Cite
|
Sign up to set email alerts
|

American Confederation of Urology (CAU) experience in minimally invasive partial nephrectomy

Abstract: Laparoscopic PN in these centers of Hispanic America seem to have acceptable perioperative complications and short-term oncologic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…In Secin et al's cohort (vs. our cohort) the median operative time was 150 min (vs. 116 min), median intraoperative bleeding 200 ml (vs. 200 ml), median tumor diameter 27 mm (vs. 27 mm), transfusion rate 10% (vs. 8.9%), median RENAL score 6 (vs. 6), and conversion rate to open partial nephrectomy 6% (vs. 0%). Also, our overall complication rates were comparable to those of Secin et al The complication rates were the following: Clavien I 5.6% (vs. 2.2%), Clavien II 8.4% (vs. 4.4%), Clavien III 4.7% (vs. 13.3%), Clavien IV 1.1% (vs. 0%), Clavien V 0% (0%) [19]. Notably, that study is multicenter (17 centers).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In Secin et al's cohort (vs. our cohort) the median operative time was 150 min (vs. 116 min), median intraoperative bleeding 200 ml (vs. 200 ml), median tumor diameter 27 mm (vs. 27 mm), transfusion rate 10% (vs. 8.9%), median RENAL score 6 (vs. 6), and conversion rate to open partial nephrectomy 6% (vs. 0%). Also, our overall complication rates were comparable to those of Secin et al The complication rates were the following: Clavien I 5.6% (vs. 2.2%), Clavien II 8.4% (vs. 4.4%), Clavien III 4.7% (vs. 13.3%), Clavien IV 1.1% (vs. 0%), Clavien V 0% (0%) [19]. Notably, that study is multicenter (17 centers).…”
Section: Discussionsupporting
confidence: 86%
“…Our perioperative metrics are in congruence with or superior to a recent multicenter study by Secin et al reporting perioperative outcomes in a large series of laparoscopic (98%) or robotic (2%) PN (n = 1501) [19]. In Secin et al's cohort (vs. our cohort) the median operative time was 150 min (vs. 116 min), median intraoperative bleeding 200 ml (vs. 200 ml), median tumor diameter 27 mm (vs. 27 mm), transfusion rate 10% (vs. 8.9%), median RENAL score 6 (vs. 6), and conversion rate to open partial nephrectomy 6% (vs. 0%).…”
Section: Discussionsupporting
confidence: 81%
“…However, recent studies within the past few decades suggest a better survival rate for women [17,18]. Recently, for LA patients who underwent minimally invasive surgery, Secin et al (2017) and Lee et al (2012) demonstrated that the mortality and local recurrence rates in women are up to four times greater than in men, resulting in a controversy [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing likelihood of malignancy and higher grade with increasing lesion size [34, 44, 45]. Of benign SRM that are surgically excised, 10–38% are found to be angiomyolipomas and 34–58% are found to be oncocytomas [4648]. Ultrasound, contrast-enhanced CT and MRI may aid diagnosis (Table 1).…”
Section: Resultsmentioning
confidence: 99%